Ideal Cardiovascular Health: Distribution, Determinants and Relationship with Health Status among People Living with HIV in Urban Tanzania. Issue 1 (12th October 2022) - Ottaru, Theresia A.; Kwesigabo, Gideon P.; Butt, Zeeshan; Rivera, Adovich S.; Chillo, Pilly; Siril, Helen; Hirschhorn, Lisa R.; Feinstein, Matthew J.; Hawkins, Claudia
Background: Ageing adults living with HIV (ALHIV) have increased risk of cardiovascular diseases as a result of HIV-infection-related chronic immune activation and inflammatory responses. Cardiovascular health index (CVHI) is a valid and relatively simple index for assessing the cardiovascular health (CVH) of the general population. Use of this index among ALHIV in Sub Saharan Africa, a resource-restricted setting where it could be mostly beneficial, remains limited. Understanding of the distribution and associated factors may inform the design of optimal interventions to improve CVH of ALHIV. Objective: We aimed to assess the distribution and factors associated with CVHI scores among ALHIV in an urban setting in Tanzania. Methods: A cross-sectional study was conducted among ALHIV on antiretroviral therapy at six HIV clinics in Dar-es-Salaam, Tanzania. We summed the score of each of the seven CVHI metric to obtain the overall CVHI score and assessed the distribution of the score by sex. We then categorized the overall score into ideal (5–7), intermediate (3–4) and poor (<3) CVH categories and performed ordinal regression to identify CVHI score associated factors. Results: In all, 629 ALHIV [mean age of 43.5(SD ± 11.2) years] were enrolled. Most had ideal levels of blood glucose (96.2%) and smoking status (83.4%) while less than half had ideal BMI (48.1%), blood pressure (BP) (43.9%) and dietary intake (7.8%). Less than half (47.6%) showed ideal CVH, while less than 1% had all seven metrics at ideal level. Older age (0.96(95%CI:0.95–0.97), p-value < 0.001), being retired/unemployed (0.59(95%CI:0.43–0.81), p-value < 0.01), being employed (0.76(95%CI:0.62–0.94), p-value = 0.01) alcohol use (0.41(95%CI:0.21–0.80), p-value = 0.01) and presence of non-communicable disease comorbidities (0.68(95%CI:0.48–0.97), p-value = 0.04) had significant lower odds of ideal CVH. Conclusion: Based on our findings, interventions to improve CVH of ALHIV should target BP management, health education on diet for BMI control and reduction in alcohol consumption, particularly among ageing ALHIV with comorbidities.